Recent Progress and Applications of Transition-Metal-Catalyzed Asymmetric Hydrogenation and Transfer Hydrogenation of Ketones and Imines through Dynamic Kinetic Resolution - Molina Betancourt, Ricardo; Echeverria, Pierre-Georges; Ayad, Tahar; Phansavath, Phannarath; Ratovelomanana-Vidal, Virginie (Synthesis, 2020)
Based on the ever-increasing demand for enantiomerically pure compounds, the development of efficient, atom-economical, and sustainable methods to produce chiral alcohols and amines is a major concern. Homogeneous asymmetric catalysis with transition-metal complexes including asymmetric hydrogenation (AH) and transfer hydrogenation (ATH) of ketones and imines through dynamic kinetic resolution (DKR) allowing the construction of up to three stereogenic centers is the main focus of the present short review, emphasizing the development of new catalytic systems combined to new classes of substrates and their applications as well.1 Introduction2 Asymmetric Hydrogenation via Dynamic Kinetic Resolution2.1 α-Substituted Ketones2.2 α-Substituted β-Keto Esters and Amides2.3 α-Substituted Esters2.4 Imine Derivatives3 Asymmetric Transfer Hydrogenation via Dynamic Kinetic Resolution3.1 α-Substituted Ketones3.2 α-Substituted β-Keto Esters, Amides, and Sulfonamides3.3 α,β-Disubstituted Cyclic Ketones3.4 β-Substituted Ketones3.5 Imine Derivatives4. Conclusion
Keywords: asymmetric hydrogenation; asymmetric transfer hydrogenation; dynamic kinetic resolution; chiral alcohols; chiral amines; enantioselectivity; diastereoselectivity